Ekstraksi Fitur Kupu-Kupu Menggunakan GLCM, Lacunarity, HSV, dan MLP - Rahayu, Putri Nur; Annisa, Aulia Rahma; Ardiana, Mirza; Andika, Yudi; Rakhmadi, Ardhon (INTEGER: Journal of Information Technology, 2025)
Extraction feature in butterflies are using GLCM, Lacunarity, and HSV. The combination of extraction feature is to improve accuration of butterflies. In this research , there are three steps for extraction. First step is extraction with GLCM and lacunarity for extraction texture, and HSV for extraction color, the second step is classification with MLP.